Minimax System Modelling and Design - Srinivasan, Thandangorai V. (My University, 1973)
Computer-aided system modelling and design for minimax objectives have been considered in detail. A new algorithm for minimax approximation, calied the grazor search method, has been proposed and successfully used on a number of network design problems to test the reliability and efficiency of the method. A critical comparison of the method with existing algorithms has shown the grazor search algorithm to be reliable in most of the problems considered. Practical ideas have been presented to deal with constrained minimax optimization problems and to investigate a solution for minimax optimality. Two user-oriented computer programs incorporating these ideas have been included as part of the thesis. Lower-order modelling of a high-order system has been considered for minimax objectives, and the suggested ideas make it feasible to design automated models for a variety of transient and steady-state constraint specifications.
Keywords: Engineering; Engineering